Metabolic, hygric and ventilatory physiology of the red-tailed phascogale (Phascogale calura; Marsupialia, Dasyuridae): Adaptations to aridity or arboreality? - Pusey, H.; Cooper, Christine; Withers, Philip (Urban und Fischer Verlag, 2013)
The red-tailed phascogale is a small arboreal dasyurid marsupial that inhabits semi-arid to arid regions of Western Australia's wheat belt. Its body mass (34.7 g) is only ~15% of that predicted based on its phylogenetic position among other dasyuromorphs; we interpret this as an adaptation to its scansorial and semi-arid/arid lifestyle. The standard physiology of this species at a thermoneutral ambient temperature of 30 °C conforms to that of other dasyurid marsupials; body temperature (34.7 ± 0.37 °C), basal metabolic rate (0.83 ± 0.076 mL O2 g-1 h-1), evaporative water loss (1.68 ± 0.218 mg H2O g-1 h-1) and wet thermal conductance (3.8 ± 0.26 J g-1 h-1 °C-1) all fall within the 95% predication limits for the respective allometric relationships for other dasyurid species. Thermolability confers an energy savings at low Ta and water savings at high Ta. Torpor, observed at low Ta, was found to be more beneficial for energy savings than for water economy. The red-tailed phascogale therefore has a physiology suitable for the challenges of arid environments without any obvious requirement for adaptations to its scansorial lifestyle, other than its considerably lower-than-expected body mass.